The Contribution Degree of Transformational Leadership to Employee Job Satisfaction in the Directorates of Education in the (Journal Of Educational and Psychological Researches, 2025)
This study aims to identify the degree to which transformational leadership contributes to employee job satisfaction within the Directorates of Education in the Sultanate of Oman. The researcher adopted the descriptive approach; the study used a questionnaire of 38 items as a primary tool. It was administered to a sample of 280 employees from the General Directorates of Education in Muscat, Al Dakhiliya, and Al Batinah South governorates. The findings revealed that both the level of transformational leadership practice and employee job satisfaction within these directorates were rated at a moderate level. The study concluded that there is a statistically significant positive correlation between all aspects of transformational leadership practice and the dimensions of job satisfaction. Furthermore, linear regression analysis demonstrated that the extent of transformational leadership practice, particularly in the areas of behaviors and spiritual values, could predict 87.9% of the variance in employee job satisfaction.